Analisis Studi Kasus Pemecatan Sepihak oleh Perusahaan Swasta - Hardo Sudiatmo; Momon Mulyana (LPPM Iblam School of Law, 2026)
This study, entitled “Case Study Analysis of Unilateral Termination by Private Companies”, aims to analyze the regulation of employment termination (PHK) under Indonesian labor law and examine the impact of unilateral dismissal on workers through case studies in the private sector. The research employs a normative juridical approach by reviewing provisions in Law No. 13 of 2003 on Manpower, Law No. 2 of 2004 on Industrial Relations Dispute Settlement, the Job Creation Law, and Government Regulation No. 35 of 2021, combined with empirical analysis of actual cases in private companies. The findings reveal that employment termination requires valid reasons, proper procedures, and legal protection for workers. In practice, however, unilateral dismissals are still frequently carried out on grounds inconsistent with legal provisions, resulting in legal uncertainty and liability for compensation on the part of employers. Furthermore, the enforcement of industrial relations court decisions is not always effective, creating a legal vacuum in execution mechanisms and a gap between normative ideals and practical realities. Therefore, strengthening regulations on the execution of industrial relations decisions and raising legal awareness among employers and employees are necessary to ensure legal certainty and the protection of workers’ rights.